(untitled) (Development Service Industry Management, 2025)
The article is devoted to the analysis of healthcare management taking into account modern terminological and conceptual approaches used in domestic and foreign practice. It is established that in Ukrainian the generalized concept of “management” prevails, covering all functions – from strategic planning to operational administration. In contrast, in international practice three key categories are clearly distinguished: governance, management and administration, each of which reflects the specifics of managerial activity at the corresponding level. In particular, governance (strategic management) covers the macro level of policy formation, control and standards, management – daily operational management of healthcare institutions, and administration – implementation of decisions at the technical and tactical levels. The feasibility of an integrated approach to the use of these terms depending on the context and functional level of managerial activity is substantiated. Special attention is paid to the construction of a healthcare institution management system in Ukraine. The concept of “healthcare facility management” is formulated as a type of management activity aimed at ensuring the effective functioning of a medical institution, including planning, organization, coordination, control and resource management. The specifics of this activity in conditions of medical and social challenges, such as epidemics or military conflicts, are considered. The multi-level structure of healthcare management in Ukraine is analyzed: national, regional, local and intra-organizational levels. Specific management entities and their functional responsibilities are given for each level. Such a distribution ensures hierarchical coherence, functional efficiency and target orientation of management decisions in the field of healthcare. The article analyzes the priorities of state policy in the field of healthcare in accordance with modern challenges and strategic goals. Fourteen key areas of transformation have been identified, including: universal access to medical services, provision of quality medicines, formation of a health culture, professional autonomy, digitalization, international integration, response to emergencies, development of human capital, etc. These areas determine the vector of modernization of the healthcare system and lay the foundation for the effective functioning of the industry in the context of reforms and integration into the European medical space.